Giant pedunculated seborrheic keratosis of penis - Thakur Jagdeep; Thakur Anamika; Chauhan CGS; Diwana Vijay; Chauhan D (Wolters Kluwer Medknow Publications, 2008)
Seborrheic keratosis of the penis is a rare entity. It has been mistaken as genital warts and differentiation is only made on histopathology. We are reporting a case presenting as multiple giant polypoidal lesions on the penile skin for the last 20 years. Seborrheic keratosis should be considered in the differential diagnosis of pedunculated lesions of the penis. The histopathology after shave excision will be diagnostic.